Sistem Informasi Online Pemesanan Dan Penyedia Informasi Jasa Percetekan Bersasis Web - Fahrijal Syawaludin (INTECH, 2023)
The printing industry has both positive and negative impacts on customers. One of the negative impacts is the inconsistent quality of printed products. To address this issue, the team developed the Web Nugraha Offset application, designed using Canva, Visual Studio Code, Notepad++, Figma, MySQL, HTML, CSS, PHP, JavaScript, and Bootstrap. This web-based application aims to help customers access information about the printing industry and its services before physically visiting the printing industry. This application's primary feature isprovidinge information on printing tools andallowing customers to orderg products online. The target audience for this application is customers who want to easily access information about printing services and products. The team's methodology involved developing a web-based application that integrates customer needs, printing industry standards, and modern web design techniques. The conclusion is that Web Nugraha Offset is an effective solution for customers seeking reliable printing services and an improved customer experience.